2021
DOI: 10.3390/ijms22115596
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of 5-Aminolevulinic Acid on Human Malignant Glioblastoma Cells

Abstract: 5-Aminolevulinic acid (5-ALA) is a naturally occurring non-proteinogenic amino acid, which contributes to the diagnosis and therapeutic approaches of various cancers, including glioblastoma (GBM). In the present study, we aimed to investigate whether 5-ALA exerted cytotoxic effects on GBM cells. We assessed cell viability, apoptosis rate, mRNA expressions of various apoptosis-related genes, generation of reactive oxygen species (ROS), and migration ability of the human U-87 malignant GBM cell line (U87MG) trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 55 publications
2
7
0
Order By: Relevance
“…Thus, a better understanding of the 5‐ALA‐mediated tumor‐regulatory mechanism brings significant benefits to patients with GBM by improving the efficacy of 5‐ALA‐based therapies. In a previous study, we demonstrated the direct tumor inhibitory effects of 5‐ALA through the regulation of proliferation, apoptosis, and migration in the U‐87 human GBM cells 39 . Consistently, in this study, we observed similar pro‐apoptotic, anti‐proliferative and anti‐migratory effects of 5‐ALA in GBM cells.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus, a better understanding of the 5‐ALA‐mediated tumor‐regulatory mechanism brings significant benefits to patients with GBM by improving the efficacy of 5‐ALA‐based therapies. In a previous study, we demonstrated the direct tumor inhibitory effects of 5‐ALA through the regulation of proliferation, apoptosis, and migration in the U‐87 human GBM cells 39 . Consistently, in this study, we observed similar pro‐apoptotic, anti‐proliferative and anti‐migratory effects of 5‐ALA in GBM cells.…”
Section: Discussionsupporting
confidence: 91%
“…In a previous study, we demonstrated the direct tumor inhibitory effects of 5-ALA through the regulation of proliferation, apoptosis, and migration in the U-87 human GBM cells. 39 Consistently, in this study, we observed similar pro-apoptotic, antiproliferative and anti-migratory effects of 5-ALA in GBM cells. In addition, 5-ALA increased the accumulation of intracellular PpIX in GBM cells, which is consistent with several other studies.…”
Section: The Effects Of Aprepitant 5-ala and Their Combination On Flu...supporting
confidence: 91%
“…Apoptosis and necrosis of U87 cells induced by UB (30 μM) were detected using the Annexin V-FITC staining kit as described previously. 20 A flow cytometric assessment was carried out on 10,000 stained U87 cells using a BD FACSCALIBUR™ FLOW CYTOMETER (Becton Dickinson). The program FlowJo V10 was used to examine the results.…”
Section: Annexin V-fitc Assaymentioning
confidence: 99%
“…5-Aminolevulinic acid (5-ALA), which induces accumulation of the protoporphyrin IX in GBM cells, is well known as the main diagnostic agent that differentiates the tumorinfiltrated tissue from adjacent healthy brain parenchyma during fluorescence-guided brain surgery [100]. Recently 5-ALA has been assigned a new role either in the context of photodynamic therapy [101] or as a direct cytotoxic agent for GBM [120]. Jalili-Nik et al report a reduction in Bcl-2 and an increase in Bax and p53 expression, and therefore an increase in apoptotic cells, in the U87MG GBM cell line after in vitro application of 5-ALA [120].…”
Section: Targeting the Cell Cycle Machinery In Gbmmentioning
confidence: 99%
“…Recently 5-ALA has been assigned a new role either in the context of photodynamic therapy [101] or as a direct cytotoxic agent for GBM [120]. Jalili-Nik et al report a reduction in Bcl-2 and an increase in Bax and p53 expression, and therefore an increase in apoptotic cells, in the U87MG GBM cell line after in vitro application of 5-ALA [120].…”
Section: Targeting the Cell Cycle Machinery In Gbmmentioning
confidence: 99%